Upaya Meningkatan Hasil Belajar Siswa Pada Mata Pelajaran Matematika Menggunakan Media Papan Penjumlahan Dan Pengurangan (Panjurang) Di Kelas Iii Sd Negeri 064974 Medan Tembung Tahun Pelajaran 2024/2025 - Simarmata, Ruth Ana Magdalena Br; Arifin, Muhammad (Peneliti.net, 2025)
This research aims to improve student learning outcomes in Mathematics subjects using the addition and subtraction board (panjurang) media for class III students at SD Negeri 064974 Medan Tembung. This type of research is Classroom Action Research (PTK), using the Kemmis and McTanggart model which includes planning, action, and observation and reflection in each cycle. The subjects in this research were class III students at SD Negeri 064974 Medan Tembung, totaling 27 students. Data collection techniques use observation and tests. The research instruments used were student observation sheets to determine the level of implementation of the learning process at each meeting, learning outcome test sheets using written questions which were used as an evaluation tool for learning activities given at the end of learning in each cycle, and data collection obtained through test results. written. Data was analyzed qualitatively and quantitatively. The indicator of success is that ≥75% of the total number of students have reached the specified KKM, namely 70. The results of the research show that the application of panjurang board media in mathematics subjects can improve the learning outcomes of class III students at SD Negeri 064974 Medan Tembung. At the time no action had been taken, the mathematics learning scores of class III students at SD Negeri 064974 Medan Tembung were only 11 (41%) students who reached the KKM score. In the first cycle of action activities, there was an increase, namely 18 (67%) students who achieved the KKM score, and in cycle II there was an increase of 25 (92%) students who succeeded in achieving the completion score. The average score of students from cycle I and cycle II increased from 65 to 84.4.